Sentiment Analysis on Import Tariff Policy and Gold Price Increase with TF-IDF - siti masripah; Rizal Amegia Saputra (Kresnamedia Publisher, 2025)
Changes in global economic policy, such as Donald Trump's import tariff policy in 2025, have generated various public responses recorded through social media such as Twitter. Analysis of this public opinion is important to understand public perception of the dynamics of gold prices as a strategic commodity. This study aims to analyze public sentiment towards the issue of tariff policies and gold using TF-IDF feature extraction. To overcome class imbalance in tweet data, the Synthetic Minority Over-sampling Technique (SMOTE) technique was used. The dataset was obtained from Twitter with the keywords